A Tumor-Targeted Nanodelivery System to Improve Early MRI Detection of Cancer - Kathleen F. Pirollo; John Dagata; Paul Wang; Matthew Freedman; Andras Vladar; Stanley Fricke; Lilia Ileva; Qi Zhou; Esther H. Chang (Molecular Imaging, 2006)
The development of improvements in magnetic resonance imaging (MRI) that would enhance sensitivity, leading to earlier detection of cancer and visualization of metastatic disease, is an area of intense exploration. We have devised a tumor-targeting, liposomal nanodelivery platform for use in gene medicine. This systemically administered nanocomplex has been shown to specifically and efficiently deliver both genes and oligonucleotides to primary and metastatic tumor cells, resulting in significant tumor growth inhibition and even tumor regression. Here we examine the effect on MRI of incorporating conventional MRI contrast agent Magnevist ® into our anti-transferrin receptor single-chain antibody (TfRscFv) liposomal complex. Both in vitro and in an in vivo orthotopic mouse model of pancreatic cancer, we show increased resolution and image intensity with the complexed Magnevist ® . Using advanced microscopy techniques (scanning electron microscopy and scanning probe microscopy), we also established that the Magnevist ® is in fact encapsulated by the liposome in the complex and that the complex still retains its nanodimensional size. These results demonstrate that this TfRscFv-liposome-Magnevist ® nanocomplex has the potential to become a useful tool in early cancer detection.